“Dimmi di che morte dobbiamo morire”: dinamiche di persuasione strutturale nel post-terremoto del Centro Italia (2016-2017) - Francesco Danesi (Archivio Antropologico Mediterraneo)
This essay analyzes the earthquake victim’s representations of the emergency response of the State in the post-disaster phase after the Italian earthquake (2016-2017). The “neglect strategy” summarizes a common understanding of the events shared by some earthquake victims. On the basis of an ethnographic research led one year after the earthquake in some of the stricken areas, the article discusses both the ambiguous logic of the institutional strategy and the activation of the emergency dispositive. Critical issues observed in the context of the disaster are explained by the concept of “structural persuasion”: a qualitative perspective enables the understanding of the local and global interactions that, as history unfolds, lead to important misrepresentations in the collective memory.